Analisis Bibliometric: Pengaruh Covid-19 terhadap Kepatuhan Wajib Pajak dan Penerimaan Pajak - Anjani, Sefiana (STIE PENA, 2023)
The purpose of this research is to find out about taxpayer compliance during the Covid-19 pandemic and how Covid-19 influences tax revenues in Indonesia. This research is a literature study using the bibliometric analysis method to analyze 200 articles related to tax revenue during the Covid-19 pandemic, which are then compiled with metadata using the Mendeley application, and the VOSviewer application is used to visualize publication data in research. Articles were obtained from the Google Scholar database accessed via Publish or Perish in the 2019-2023 range with defining the keywords 'Covid-19' and 'Tax'. The results of the study show that the research classification regarding tax revenue during the Covid-19 pandemic is divided into 4 specific words with topics centered on tax incentives, the Covid-19 pandemic, Covid-19 and taxpayer compliance. The Covid-19 pandemic that hit Indonesia has had an impact on the people's economy so the people's ability to carry out their tax obligations has also decreased. Therefore, this research was conducted to find out how influential Covid-19 was on taxpayer compliance and tax revenue in Indonesia. Then what policies should be made to overcome the impact of the pandemic and the methods used to increase tax compliance.Keywords: Covid-19; Insentif pajak; Kepatuhan wajib pajak